Uji Efektivitas Antibiotik Ekstrak Etanol Daun Kayu Manis (Cinnamomum burmannii) terhadap Pertumbuhan Bakteri Staphylococcus sureus dan Escherichia coli secara In Vitro - Sang Ayu Bulan Dirga Pradnyani; Risma Ikawaty; Sajuni Widjaja; Sang Ketut Sudirga (Metamorfosa: Journal of Biological Sciences, 2026)
Bacterial infections caused by S. aureus and E. coli remain a major global health problem. Irrational antibiotic use has accelerated antimicrobial resistance, prompting the search for alternative antibacterial agents derived from natural products. Cinnamon leaves (Cinnamomum burmannii) contain various secondary metabolites with potential antibacterial activity. This study aimed to evaluate the antibacterial activity of ethanolic cinnamon leaf extract against S. aureus and E. coli in vitro and to determine the most effective extract concentration. This laboratory-based true experimental study employed a post-test only control group design. Cinnamon leaf extract was prepared by maceration using 96% ethanol. Antibacterial activity was assessed using the well diffusion method on Mueller Hinton Agar at extract concentrations of 25%, 50%, 75%, and 100%. Ciprofloxacin served as the positive control, while 96% ethanol was used as the negative control. Phytochemical screening and antioxidant activity testing (DPPH method) were also performed. Data were analyzed using One-Way ANOVA followed by Duncan post-hoc test. Result : Phytochemical screening revealed the presence of flavonoids, alkaloids, tannins, saponins, and phenolic compounds, with phenols as the dominant constituents. The extract exhibited moderate antioxidant activity based on IC₅₀ values. Antibacterial testing demonstrated that ethanolic cinnamon leaf extract inhibited the growth of both S. aureus and E. coli, with inhibition zones increasing in a concentration-dependent manner. The 75% concentration demonstrated optimal inhibitory activity, with no statistically significant difference compared to the 100% concentration (p > 0.05). Ethanolic cinnamon leaf extract (Cinnamomum burmannii) shows promising antibacterial activity against S. aureus and E. coli in vitro, indicating its potential as a natural antibacterial agent.